Uso de reator aeróbio de leito fluidizado com circulação como dispositivo de pós-tratamento do efluente de um reator uasb compartimentado tratando esgotos sanitários - Tetila, Moacir Feba [UNESP] (2015)
The study used an aerobic fluidized bed reactor with circulation (RALFC) as the effluent post-treatment device of a UASB reactor Compartmented (RUC) which treated wastewater. The RUC was consisted of 4 PVC tubes of different diameters arranged concentrically and RALFC two PVC tubes of different diameters and concentric, and a sedimentation unit in the upper part. The research was divided into four distinct phases and starting, called Phase 1A, 1B, 2A and 2B, in which were various operating parameters such as air flow, flow of wastewater, hydraulic retention time (HRT) and volumetric organic load (VOC). So that during the research it was found that the best treatment phase was when the RALFC operated with HRT of 4.7 hours and air flow of 300 L / h. The system, at this stage, had an average effluent COD value of 55 mg/L, from the affluent valor of 607 mg/L on average, there by generating a complete removal of 90%. The control parameters as alkalinity, pH, temperature and volatile organic acids have always been within the recommended by the literature, demonstrating a low oscillation. Even so, the system hasn't showed good performance in the removal of nutrients, in their best treatment stage an effluent with 31 mg/L on average total nitrogen from an input value of 50 mg/L. The most part of nitrogen removal was during passage through the RUC. As for the phosphorus values were 25 mg/L in the effluent input and 14 mg/L, in the same as was the nitrogen, the majority of phosphorus removal was performed by RUC